The Contestation of Power Between Newsrooms and Media Owners in Television Stations in Indonesia - Sonni, Alem Febri; Hijjang, Pawennari; Tahara, Tasrifin; Sultan, M. Iqbal (International Journal of Global Community, 2018)
This article describes the contest for power and influence that goes on behind the scenes of Indonesian television broadcasting stations. There is a dynamic relationship between agent and structure –journalists and media owners –in news broadcasting in Indonesian television stations. The newsroom was previously idealised as an independent, neutral space free from intervention, but its independence has been eroded by political contestations involving media owners. Politics relies greatly on the dissemination of information to rally support from constituents. Television is currently the most powerful medium for that purpose. This research is a qualitative study that obtained data from two of Indonesia’s largest television stations, Metro TV and TV One. Data collection involved literature review, observation, and in-depth interviews. The obtained data was analysed in three steps: (1) data processing, (2) data reduction, and (3) data display to allow for conclusion drawing. The results of this research show that media owners have significant influence over the content of news broadcasts. This is largely due to a lack of strict government legislation guaranteeing newsroom independence from capital influences that exist in the television industry. Indonesian culture also plays a role in how powerful the regulations that protect the interests and policies of capitalists are.